Synergistic effect of bovine platelet lysate and various polysaccharides on the biological properties of collagen-based scaffolds for tissue engineering: Scaffold preparation, chemo-physical characterization, in vitro and ex ovo evaluation - Babrnáková, Johana; Pavliňáková, Veronika; Brtníková, Jana; Sedláček, Petr; Prosecká, Eva; Rampichová, Michala; Filová, Eva; Hearnden, Vanessa; Vojtová, Lucy (Materials science & engineering. C, Materials for biological applications, 2019)
Crosslinked 3D porous collagen-polysaccharide scaffolds, prepared by freeze-drying, were modified with bovine platelet lysate (BPL) and evaluated in terms of chemical, physical and biological properties. Natural antibacterial polysaccharides like chitosan, chitin/chitosan-glucan complex and calcium salt of oxidized cellulose (CaOC) incorporated in collagen scaffolds affected not only chemo-physical properties of the composite scaffolds but also improved their biological properties, especially when BPL was presented. Lipophilic BPL formed microspheres in porous scaffolds while reduced by half their swelling ratio. The resistance of collagen sponges to hydrolytic degradation in water depended strongly on chemical crosslinking varying from 60 min to more than one year. According to in-vitro tests, chemically crosslinked scaffolds exhibited a good cellular response, cell-matrix interactions, and biocompatibility of the material. The combination of collagen with natural polysaccharides confirmed a significant positive synergistic effect on cultivation of cells as determined by MTS assay and PicoGreen method, as well as on angiogenesis evaluated by ex ovo Chick Chorioallantoic Membrane (CAM) assay. Contrary, modification only by BLP of pure collagen scaffolds exhibited decreased biocompatibility in comparison to unmodified pure collagen scaffold. We propose that the newly developed crosslinked collagen sponges involving bioactive additives could be used as scaffold for growing cells in systems with low mechanical loading in tissue engineering, especially in dermis replacement, where neovascularization is a crucial parameter for successful skin regeneration.
Keywords: Cross-Linking Reagents; Tissue Engineering; Hydrolysis; buňky 3T3; Chitosan; tkáňové inženýrství; Chickens; Temperature; fyziologická neovaskularizace; hydrolýza; Angiogenesis; teplota; trombocyty; Tissue Scaffolds; Cell Adhesion; kolagen; zvířata; reagencia zkříženě vázaná; proliferace buněk; myši; Collagen; Mice; Blood Platelets; kur domácí; 3T3 Cells; Cattle; tkáňové podpůrné struktury; Cell Proliferation; voda; skot; Fibroblast proliferation; Oxidized cellulose; fibroblasty; Water; Animals; buněčná adheze; Polysaccharides; polysacharidy; Neovascularization, Physiologic; Bovine platelet lysate; Fibroblasts